Bone Morphogenetic Proteins: Structure, biological function and therapeutic applications - Carreira, Ana Claudia; Alves, Gutemberg Gomes; Zambuzzi, William Fernando [UNESP]; Sogayar, Mari Cleide; Granjeiro, Jose Mauro (Elsevier B.V., 2014)
Bone Morphogenetic Proteins (BMPs) are multifunctional secreted cytokines, which belong to the TGF-beta superfamily. These glycoproteins act as a disulfide-linked homo- or heterodimers, being potent regulators of bone and cartilage formation and repair, cell proliferation during embryonic development and bone homeostasis in the adult. BMPs are promising molecules for tissue engineering and bone therapy. The present review discusses this family of proteins, their structure and biological function, their therapeutic applications and drawbacks, their effects on mesenchymal stem cells differentiation, and the cell signaling pathways involved in this process. (C) 2014 Published by Elsevier Inc.
Keywords: Bone Morphogenetic Proteins; Osteogenesis inducing proteins; Peptide growth factors; Bone repair; Extracellular matrix; Tissue engineering